Benjamim e Beautiful Losers: a memória e a (des)construção da imagem do feminino - Mata, Lorena Silva da (2016)
This work’s purpose was to consider, comparativly, female representation models disposed on Benjamim and Beautiful Losers narratives throughout the desconstructivist aspect fomented by memory, since this, that presents itself as an artifice to the narrative construction, manifest female reality representation in the corpus selected to our analisys as a problem. Memory, more than the female, presents itself as the central problem in these stories which impels the biographic overthrow of male characters created, respectively, by Chico Buarque and Leonard Cohen. Furthermore, for its ambiguity feature, the notion of memory enables the deconstruction of universal truths related by several fields of human sciences. The thesis that rises from this research corroborates with the deconstruction idea of universal models for female representation, guided by steriotype construed in a patriarcalism scope, makeing possible to dislocate the operationalized and semiotised truth by which history’s and cultural’s discursive codes configures social individuals. Thus, considering other extrinsic and not immediatly textual perspectives in these fictions, and comparing them in its similarity and differences, it is possible to comprehend these narratives in its critics dimension, on which the moment of female image desconstruction makes possible rereading universal models regulated by a group usually seen as a dominant one.